A institucionalização da educação ambiental no Programa Mais Educação: análise dos projetos setoriais desenvolvidos no Núcleo Regional de Educação de Toledo. - Fernandes, Cristiane Weirich (2016)
The growth and development of economic activities based on unsustainable consumption of natural resources has triggered discussions of social, political, cultural and environmental, demanding that the environmental debate would come to consider the complex relationships between natural and social aspects, including the environment as the result of these relationships. The socializing function of contemporary school brings environmental issues to the education system, through the institutionalization of environmental education from public policies and, most often, through educational programs and projects. One of the institutional programs recently implemented in public schools is the More Education Program, which aims at the integral formation of the students, indicating the expansion of time and educational activities, through educational activities directed to environmental issues (among others). Whereas it is important to determine the design of Environmental Education established by the More Education Program, there was documentary research presented by this dissertation. After making a brief theoretical framework of concepts and educational and environmental practices in the school context and understand the deployment process and operation of the program, using the Laurence Bardin content analysis technique, it is possible to say that the institutionalization of Environmental Education through the More Education Program shows the breakdown of the concepts and fundamentals of environmental education, because although the program has arisen from the government an excuse to interweave education and social policies in order to establish inter-ministerial actions, their own implementation induces the compartmentalization of knowledge, as opposed to interdisciplinary principles of Environmental Education and integral Education, considered essential to a comprehensive quality training. Thus the More Education Program does not extend the practical view of environmental education in schools, only confirms the maintenance and expansion of practices that have as a result reduced environmental concepts, reinforcing the conservationist bias of Environmental Education.